Analysis of Contribution Tuna Cakalang Tongkol (TCT) on Regional Bruto Domestic Revenues in Tulungagung Regency - Satria Kushendarto; Mochammad Fattah; Mariyana Sari; Wildan AlFarizi (Faculty of Fisheries and Marine Science, Brawijaya University, 2018)
The objectives of this research: 1) to analyze the contribution of tuna, tuna and skipjack to gross regional domestic income, 2) to estimate the development of tuna, tuna and skipjack tuna production. The method used in this study is quantitative and secondary data types sourced from BPS and DKP with data collection techniques documentation. Quantitative data analysis in this research is contribution analysis and quadratic trend. The average contribution of TCT fish to PDRB of Tulungagung Regency is 0.0006%. Estimated production from 2017-2026 tuna has an average production increase of 32%, skipjack tuna has an average production increase of 31% and tuna has an average production increase of 43%.The increased production of TCT fish expected sees the sustainability of ecology by the use of the think that environmentally friendly and considers value optimal the use of commodities TCT fish.